Optimasi Proses Pembuatan Bubuk (Tepung) Kedelai - Rani, Hertini; Zulfahmi, Zulfahmi; Widodo, Yatim R. (Jurnal Penelitian Pertanian Terapan, 2013)
Soybean powder is processed soy products are created through several stages of processing, such as sorting, soaking, cooking, refrigeration, drying, grinding, sieving and, packaging.This study aimed to determine the effect of dipping time and pressing time on the quality of soybean powdering. This research was arranged in a randomized block design (RAK) consists of 2 factors. The first factor is a long soaking soybeans (L1 = 0 hours; L2 = 3 hours; L3 = 6 hours, and L4 = 9 hours). The second factor is long pressing time (P1 = 0 minutes; P2 = 5 minutes; P3 = 10 minutes, and P4 = 15 minutes). This study consisted of 8 treatment combinations with three replications.The results of this study, namely the process of soaking soybeans for 3 hours produces yield 72.80% degree of whiteness 53.37%. Protein content 32.86 %, fat 25.22 % ALB 7.77%, and 4.2 % water. While soybeans pressing process for 5 minutes produces rendemen 75.29 %, 44.03 % degree of whiteness. Protein contentof 32.78%, 26.45% fat, ALB 4.67 %, and water 5:12 %. Key words: soybean flouring, dipping, pressing condition